2012
DOI: 10.1021/bc3003919
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Low Molecular Weight Fluorescent Imaging Agents for the Prostate-Specific Membrane Antigen

Abstract: Targeted near-infrared (NIR) optical imaging can be used in vivo to detect specific tissues, including malignant cells. A series of NIR fluorescent ligands targeting the prostate-specific membrane antigen (PSMA) was synthesized and each compound was tested for its ability to image PSMA+ tissues in experimental models of prostate cancer. The agents were prepared by conjugating commercially available active esters of NIR dyes, including IRDye800CW, IRDye800RS, Cy5.5, Cy7, or a derivative of indocyanine green (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
72
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 41 publications
8
72
1
1
Order By: Relevance
“…Other studies where fluorophores of intermediate polarity to IRDye800 and Cy5.5 were conjugated to PSMA-1 showed still different in vivo kinetics (data not shown), suggesting that polarity of the fluorophore might dramatically influence pharmacokinetics of the agents. The phenomenon that a particular NIR dye can affect the pharmacokinetics of a conjugated probe was also reported by Chen and colleagues (30). They observed that more hydrophobic probe has longer retention time in the body, consistent with our findings.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Other studies where fluorophores of intermediate polarity to IRDye800 and Cy5.5 were conjugated to PSMA-1 showed still different in vivo kinetics (data not shown), suggesting that polarity of the fluorophore might dramatically influence pharmacokinetics of the agents. The phenomenon that a particular NIR dye can affect the pharmacokinetics of a conjugated probe was also reported by Chen and colleagues (30). They observed that more hydrophobic probe has longer retention time in the body, consistent with our findings.…”
Section: Discussionsupporting
confidence: 61%
“…The first small-molecule–based PSMA targeting imaging agent was reported in 2005 by Humblet and colleagues (20). Since then many small molecular PSMA-targeting imaging agents have been developed for single-photon emission tomography (SPECT), PET, and optical imaging (2130). Among these imaging agents, the urea-based 18 F-DCFBC (25, 31, 32), 123 I-MIP-1072 (26), and 123 I-MIP-1095 (33) have entered into clinical trials and shown the ability to detect both bone and soft-tissue metastases in patients with prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…57,1922 When KUE was conjugated directly with ZW800-1, however, no membrane binding was observed on LNCaP cells in vitro and in vivo (data not shown). This result indicates that the conjugated fluorophore agitates the favorable pharmacokinetic property of targeted ligand.…”
mentioning
confidence: 95%
“…1,2 Many efforts have been made to detect and treat primary and metastatic prostate cancers using PSMA-based targeting such as computed tomography, nuclear imaging, and magnetic resonance imaging. 37 Despite the recent advancement in nuclear medicine-based therapy, surgical resection remains a definitive treatment for prostate cancer. 1,8 Compared to PSMA-targeted nuclear medicine, optical imaging could provide real-time guidance during prostate resection with highly sensitive, rapid, and non-radioactive NIR fluorescence light, and importantly, highlight areas of extracapsular extension or in-transit metastases.…”
mentioning
confidence: 99%
See 1 more Smart Citation